2016
DOI: 10.56093/ijans.v86i12.65963
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting conception rates in AI bred buffaloes in field conditions

Abstract: The objective of the study was to identify the factors affecting variation in conception rate of buffaloes inseminated by Murrah bulls’ frozen semen under field conditions. Total of 18,396 insemination records pertaining to 11,793 buffaloes that were inseminated artificially at BAIF’s field AI centers during the period of June 2010 to December 2014 in 3 states. Logistic regression analysis was used to compute the odds ratio and probability of conception rate. Records were classified according to agroclimatic z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…It was significantly (p<0.005) differed from each other. www.extensionjournal.com The expression of estrus in the present study are supported by Malik et al (2011) [32] , Parmar et al (2014) [37] , Thangapandiyan et al (2015) [53] and Kumar et al (2016) [28] , they recorded a100% estrus response by norgestomet + PMSG treated anestrus buffaloes under farm conditions. It was observed that the combined effect of progesterone priming of the brain for estradiol receptors and high endogenous estradiol with PMSG administration mainly responsible for behavioral signs (Cavalieri et al 1995) [16] .…”
Section: Conception Ratesupporting
confidence: 85%
See 2 more Smart Citations
“…It was significantly (p<0.005) differed from each other. www.extensionjournal.com The expression of estrus in the present study are supported by Malik et al (2011) [32] , Parmar et al (2014) [37] , Thangapandiyan et al (2015) [53] and Kumar et al (2016) [28] , they recorded a100% estrus response by norgestomet + PMSG treated anestrus buffaloes under farm conditions. It was observed that the combined effect of progesterone priming of the brain for estradiol receptors and high endogenous estradiol with PMSG administration mainly responsible for behavioral signs (Cavalieri et al 1995) [16] .…”
Section: Conception Ratesupporting
confidence: 85%
“…The animals however suffer from inherent reproductive problems such as poor estrous expression and long calving intervals which limits its lifetime production specially in summer season (Prakash et al 2005) [42] . In addition, the incidences of silent heat are higher in summer than winter months (Khattab et al 1990;Tailor et al, 1990;Kassim and Nany, 1999;Prakash, 2002) [27,53,26,43] . In general, reproductive activity of buffaloes is mainly determined by day length, climate (ambient temperature and relative humidity) and nutrition (Singh et al 2000;Vale et al 2019) [50,56] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation